Strategi Guru dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Tematik Kelas V di SD Negeri Sidodadi, Kecamatan Kampung Rakyat, Kabupaten Labuhan Batu Selatan - Arlina, Arlina; Mazid, Miftah Ilham; Apriani, Suci; Cahyani, Vira Regina; Sanjuwatma, Delvi; Harahap, Sandi Mahatir (Lembaga Yasin AlSys, 2023)
The learning strategy is a plan that summarizes a series of learning activities in the learning process such as student management, teacher management, learning activity management, and learning environment management. Therefore, to achieve educational goals in education, teachers must have several strategies to improve student learning outcomes. The questions posed in this research are: What are the teacher's strategies in improving student learning outcomes in thematic education in Siddadi Colorado State? This study used descriptive qualitative method. Data collection is done through observation, interviews and documentation. The results of this study indicate that educators need to actively participate in activities carried out by the government and schools, such as training, advanced training, and seminars related to learning strategies. This is done to help teachers understand how to apply teaching strategies and how to use existing teaching methods and media to motivate students to participate in learning. As with any initiative to improve student learning outcomes, there are always barriers to strategy implementation. Therefore, teachers must be able to overcome this and minimize it to improve student learning outcomes. Parental support is also very helpful for teachers in improving student learning outcomes. Therefore, teachers and parents of students must work together.